Cephalic and extracephalic neurophysiological effects of botulinum toxin type A in chronic migraine. Issue 1 (January 2019) - Coppola, G.; Cortese, F.; Di Lenola, D.; Di Lorenzo, C.; Parisi, V.; Pierelli, F.
Abstract : The neurophysiological mechanisms underlying clinical efficacy of botulinum toxin type A (BTX-A) treatment of chronic migraine (CM) are still debated widely. We assessed the cephalic, and extra-cephalic effects of BTX-A injection in a group of 13 CM patients, by simultaneously recording the blink reflex (nBR), the trigemino-cervical reflex (nTCR), and the pain-related evoked potential (PREP) following stimulation of the right supraorbital nerve, and by recording the non-noxious somatosensory evoked potentials (SSEPs). Neurophysiological measurements were recorded before, and 1 month and 3 months after BTX-A. At month 3, BTX-A significantly reduced the mean headache days, severity of headache, and tablet intake. A significant increase in pain threshold was noted 3 months after treatment compared to baseline. We found that the initial nBR and nTCR lack of habituation was replaced by normal habituating response at 3 months. There were no variations in the initial PREP and SSEP after BTX-A, despite a trend for an increased habituation for PREP and lack of SSEP amplitudes. Our findings suggest that the responsiveness to a single session of BTX-A may be related to the blockage of sensitization of the nociceptive neurons in the dorsal horn, without an evident involvement of cortical circuitries.